TEACHING READING NARRATIVE TEXT BY USING RECIPROCAL TECHNIQUE - Maharani, Kartika; Sudarsono, Sudarsono; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to find out the effectiveness of reciprocal technique to teach narrative texts to the Year-10 students of SMK Cahaya Bangsa in Academic Year 2018/2019. The research participants were Class X Pharmacy which consisted of 25 students. The data were collected through a written test. The finding showed that the studentsâ€™ mean score of post-test (72) was higher than that of pre-test (56). Statistically the t-test (11.58) was higher than the t-table (0.381) and the effect of the treatment was categorized strong (2.31). In short, the use of Reciprocal Technique affects the teaching of narrative texts significantly. Therefore, the alternative hypothesis which stated â€œReciprocal Technique affects the teaching of reading comprehension of narrative texts to the Year-10 students of â€œSMK Cahaya Bangsa Rasau Jaya in Academic Year 2018/2019â€ was accepted. Â Keywords: Reading, Narrative Text, Reciprocal Technique